2017
DOI: 10.1111/bcpt.12852
|View full text |Cite
|
Sign up to set email alerts
|

Huprine X Attenuates The Neurotoxicity Induced by Kainic Acid, Especially Brain Inflammation

Abstract: Huprine X (HX) is a synthetic anticholinesterasic compound that exerts a potent inhibitory action on acetylcholinesterase (AChE) activity, an agonist effect on cholinergic receptors, neuroprotective activity in different neurotoxicity models in vivo and in vitro and cognition enhancing effects in non-transgenic (C57BL/6) and transgenic (3xTg-AD, APPswe) mice. In this study, we assessed the ability of HX (0.8 mg/kg, 21 days) to prevent the damage induced by kainic acid (KA; 28 mg/kg) regarding apoptosis, glia r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Neurogenesis decreases during neurodegenerative disease and the aging process as well. As it was observed in the case of huprine X [ 14 ], treatment with AVCRI104P3 did not change the expression of the neurogenesis marker DCX in the DG of the hippocampus under the present experimental conditions. This is in contrast to previous reports where it was observed that the AChEIs donepezil, rivastigmine, and galantamine were able to stimulate neurogenesis in different mouse models [ 50 ].…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Neurogenesis decreases during neurodegenerative disease and the aging process as well. As it was observed in the case of huprine X [ 14 ], treatment with AVCRI104P3 did not change the expression of the neurogenesis marker DCX in the DG of the hippocampus under the present experimental conditions. This is in contrast to previous reports where it was observed that the AChEIs donepezil, rivastigmine, and galantamine were able to stimulate neurogenesis in different mouse models [ 50 ].…”
Section: Discussionsupporting
confidence: 74%
“…In this study, it was determined whether the anticholinesterasic AVCRI104P3 could modify the expression of cerebral inflammatory protein markers such as GFAP and Iba1 as it is known that activation of nicotinic receptor is involved in anti-inflammatory mechanisms [ 46 ]. Indeed, we previously observed an anti-inflammatory effect of huprine X in the kainic acid mouse model [ 14 ]. In this work, we have observed that AVCRI104P3 did not modify the astrogliosis marker (GFAP), even though it significantly reduced the expression of the activated microglia protein marker (Iba-1) (34%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations